MAGEA6 Engages a YY1‐Dependent Transcription to Dictate Perineural Invasion in Colorectal Cancer - Hao Wang; Kexin He; Ruixue Huo; Weihan Li; Shan Zhang; Lu‐Ju Jiang; Hao Wu; Minhao Yu; Shu‐Heng Jiang; Junli Xue (Advanced Science)
Abstract Perineural invasion (PNI), characterized by tumor cells surrounding and invading nerves, is associated with poor prognosis in colorectal cancer (CRC). Understanding the mechanisms of PNI is crucial for developing targeted therapies to impede tumor progression. In this study, clinical information and transcriptome data are obtained from the TCGA database. Stable MAGEA6 knockdown CRC cell lines are established to investigate the impact of MAGEA6 on CRC malignancy. Immunohistochemical staining is used to assess the clinical significance of MAGEA6. Rectal orthotopic and sciatic nerve invasion models are employed to verify the role of MAGEA6 in PNI. Schwann cells (SCs) infiltration and recruitment by CRC cells are assessed using ssGSEA and co‐culture experiments. The results reveal that MAGEA6 is a key regulator of PNI, with its expression correlating with poor prognosis. MAGEA6 knockdown reduces CRC cell migration, invasion, and PNI ability. Moreover, CRC cells recruit SCs, with CXCL1 promoting SCs migration. Mechanistically, MAGEA6 inhibits YY1 ubiquitination, stabilizing YY1 expression and enhancing SC recruitment via YY1‐mediated CXCL1 transcription. These findings suggest that MAGEA6 enhances CRC invasiveness and PNI by stabilizing YY1, which upregulates CXCL1 secretion and promotes SC recruitment. This interaction underscores the critical role of MAGEA6 in PNI and highlights a potential therapeutic target in CRC.